2021
DOI: 10.21203/rs.3.rs-508725/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving the Mechanical Properties of Ramie-Polylactic Acid Green Composites by Surface Modification using Single Bath Alkaline and Silane Treatment

Abstract: This research work emphasises on improving the interfacial adhesion of ramie/ polylactic acid (PLA) composites. For this purpose, ramie fabric was modified using vinyl trimethoxy silane with two different hydrolysing agents, i.e. sodium hydroxide and ammonia. The surface modified ramie fabric was characterised by static water contact angle, elemental dispersive X-ray (EDX) and Fourier transform infrared spectroscopy (FTIR). FTIR and EDX analysis confirmed the presence of silica. The tensile strength of fabric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The outcome showed that the alkali process's elimination of contaminants like lignin and hemicellulose considerably lowers the ramie fibres diameter and prevents defibrillation [19]. It is well known that ramie fibres have potent hydrophilic qualities [20]. The hydrophilic group on the surface of ramie fibres ameliorates when they were treated with increasing concentrations of alkali, which enhanced the fibre's ability to absorb water [18].…”
Section: Resultsmentioning
confidence: 99%
“…The outcome showed that the alkali process's elimination of contaminants like lignin and hemicellulose considerably lowers the ramie fibres diameter and prevents defibrillation [19]. It is well known that ramie fibres have potent hydrophilic qualities [20]. The hydrophilic group on the surface of ramie fibres ameliorates when they were treated with increasing concentrations of alkali, which enhanced the fibre's ability to absorb water [18].…”
Section: Resultsmentioning
confidence: 99%